Competition, governance, and relationship‐specific investments: Theory and implications for strategy - Jia, Nan (Strategic Management Journal, 2013)
This paper uses biform games to examine the endogenous decision to invest in relationship‐specific assets. It addresses the questions of how competition affects suppliers' decisions to produce a general‐purpose product or a relationship‐specific product for a buyer and under what circumstances a governance arrangement designed to share investment costs between the transacting parties increases the investment in relationship‐specific assets. We offer a balanced perspective that emphasizes both the superior transaction value of relationship‐specific products and their high transaction costs while considering the competition effects generated by alternative investment plans. The model and its extensions generate new insights into investment decisions regarding relationship‐specific assets . Copyright © 2013 John Wiley & Sons, Ltd.